Finding me - Davis, Viola 1965- (HarperOne, an imprint of HarperCollinsPublishers, 2023)
In my book, you will meet a little girl named Viola who ran from her past until she made a life changing decision to stop running forever. This is my story, from a crumbling apartment in Central Falls, Rhode Island, to the stage in New York City, and beyond
"Oprah's book club 2022"--Cover page
Keywords: Davis, Viola / 1965-; African American actresses / Biography; African American actresses / United States / Biography; African American actors / Biography; African American women / Biography; Actresses / Biography; Self-realization in women; Actresses; African American actors; African American actresses; African American women; United States; Autobiographies; Biographies; Autobiografie